PENYULUHAN TENTANG KEWENANGAN PEMERINTAH DALAM PENGEMBANGAN PENDIDIKAN BERDASARKAN UNDANG- UNDANG NO. 20 TAHUN 2003 DI YAYASAN PERKASA KARUNIA LUHUR TANGERANG - Rahim, Abdur; Almadani, Husna Aulia; Ramadhan, Dieni; Jannah, Indah Ismaul; Sakinah, Nabila; Wulansari, Tri Utami; Ulhaq, Dhiya; Haq, Dipa Dinul (LPPM Universitas Bina Bangsa, 2024)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self- control, personality, intelligence, noble morals, and the skills needed by themselves, society, nation and state. The national education system is all educational components that are interconnected in an integrated manner to achieve national education goals. This Community Service activity aims to provide legal counseling assistance related to educational development to the community, especially the Tangerang community. The title of this activity is